Runoff simulation and projection in the source area of the Yellow River using the SWAT model and SSPs scenarios - Li, Xiehui; Jia, Hejia; Chen, Yaling; Wen, Jun (Frontiers in Environmental Science, 2022)
The source area of the Yellow River (SAYR) is one of the regions with the larger wetland area and the most abundant wetland types at high altitudes in the world, and its response to climate change is extremely significant. Simulation and projection of future changes in runoff in the SAYR have important strategic value for the macro-control of water resources and wetland eco-environmental protection. In the present investigation, we selected runoff and related meteorological data corresponding to SAYR from 1976 to 2014. In addition, Digital Elevation Model (DEM), land-use, and soil data were used considering three future scenarios of Norwegian Earth System Model version 2 (NorESM2_MM) obtained from the Coupled Model Intercomparison Project Phase 6 (CMIP6) from 1976 to 2100. The Soil and Water Assessment Tool (SWAT) was used to simulate, project, and analyze potential variations and future runoff of three main hydrological stations (Jimai, Maqu, and Tangnaihai) located in the SAYR. The results showed that: (1) The SWAT model displayed good applicability in historical runoff simulation in the SAYR. A small runoff simulation uncertainty was observed, and the simulated value was close to the measured value. (2) Under three 2021-2100 scenarios, the yearly discharge of the three hydrological stations located in the SAYR showed a slight increasing trend. Precipitation is the main factor affecting future runoff. (3) We compared the 1976-2014 average annual runoff with the projected values corresponding to the periods 2021-2060 and 2061-2100. With respect to 2021-2060, data indicated that the lowest and highest increase occurred under the SSP245 and the SSP126 scenarios, respectively. Moreover, for 2061-2100, the lowest and highest increase happened under the SSP126 and the SSP585 scenarios, correspondingly. The yearly average discharge in the near future will be smaller than that in the far future.